Intercultural Communication in EFL Classrooms - Markus Deli Girik Allo (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
Intercultural communication is an important aspect in EFL classrooms since EFL classrooms are one of the learners’ environments to learn the culture and intercultural communication. The researcher employed the quantitative research with survey design. This study investigated the place of culture and intercultural communication in Torajan EFL classrooms and Torajan students’ perceptions on Imperatives for studying Intercultural Communication. It is found that: Students needed for the new cultural and intercultural knowledge in EFL classrooms and hoped that curriculum can meet their needs on intercultural communication competence, and students are aware and hope to institutional and EFL lecturers to create intercultural environment and encourage effective intercultural dialogue in EFL classrooms in order to achieve: pedagogical, personal development, peace, economic, demographic, and ethical imperatives of intercultural communication.